1995
DOI: 10.1288/00005537-199502000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body tumors: A review of 30 patients with 46 tumors

Abstract: Minimal morbidity occurs with resection of most carotid body tumors (CBT). With larger tumors significant injury to the cranial nerves has been reported. In order to assess the operative sequelae rate, 30 patients with CBT were reviewed. Sixteen patients either presented with bilateral carotid body tumors or had previously undergone a resection of the contralateral carotid body tumors, for a total carotid body tumor count of 46. Sixteen patients demonstrated a familial pattern while 14 were nonfamilial. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
110
0
8

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(125 citation statements)
references
References 25 publications
0
110
0
8
Order By: Relevance
“…Since most of the Shamblin's III cases included in this study could be considered as class IIIa, it was expected to have some of them successfully excised without vascular resection. The distinction between vascular encasement and vascular infiltration should be clear when interpreting the outcomes of resection of Shamblin III makes precise periadventitial dissection more difficult 28) and the risk of intracranial embolization. 20) Also it did not affect the probability of need for vascular repair.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the Shamblin's III cases included in this study could be considered as class IIIa, it was expected to have some of them successfully excised without vascular resection. The distinction between vascular encasement and vascular infiltration should be clear when interpreting the outcomes of resection of Shamblin III makes precise periadventitial dissection more difficult 28) and the risk of intracranial embolization. 20) Also it did not affect the probability of need for vascular repair.…”
Section: Discussionmentioning
confidence: 99%
“…Type I cells (also called glomus or epitheloid cells), measure changes in blood pressure and the composition of arterial blood flowing past them, including the partial pressures of oxygen and carbon dioxide and are also sensitive to changes in blood temperature and pH, suggesting that they are secretory cells. [7][8] The type II cells (also called sustentacular or supporting cells) resemble glial cells of the nervous system. 9 Previous investigation showed that the carotid bodies enlarge in cattle, guinea-pigs and rabbits living in the hypobaric hypoxia of high altitude to which they have to acclimatize.…”
mentioning
confidence: 99%
“…10 During the procedure, before dissection, it is very important to identify and fully expose all nerves, avoiding excessive handling. 5,23 In certain situations, such as resection en bloc or a possible injury to the artery wall, it will be necessary to construct a shunt. 17 Barbiturates and mannitol are recommended if it is necessary to clamp the internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
“…25 The greatest cause of morbidity is injury to the cranial pairs, of which the hypoglossal, vagus and laryngeal superior are the most often affected, which can cause paralysis that is very often definitive. 4,17,18,23 More serious complications, such as strokes and difficult to control hemorrhages, are rarer. 4 Embolization can be employed in cases of large tumors, which will reduce blood loss and the size of the tumor and improve the results of surgery, but the risk of cerebral embolism cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%